Antiarrhythmic drugs use in elderly patients. Vaughan Williams class I and II drugs - E. A. Ushkalova; S. K. Zyryanov; K. E. Zatolochina; A. P. Pereverzev; N. A. Chukhareva (Рациональная фармакотерапия в кардиологии, 2016)
Use of class I antiarrhythmic drugs in the elderly is limited by their adverse drug reactions (ADRs), proarrhythmic effect (I A и I C) and high risk of drug interactions. Disopyramide use should be avoided due to its strong anticholinergic properties associated with the risk of cognitive and physical disorders and falls in the “very elderly” patients. Available data suggest that elderly patients do not have significant limitations for beta-blockers use. However to determine beta-blockers with the best benefit/risk ratio in elderly patients with co-morbidity further clinical trials are needed.